Iron Administration Affects Cardiac Calcium Channel Expression in Mice: The Role of Cardiac Calcium Channel Expression in The Heart of Iron Overload Mice Model - Mas Rizky Anggun Adipurna Syamsunarno; Alif Bagus Rakhimullah; Uni Gamayani; Masahiko Kurabayasi; Tatsuya Iso; Ratu Safitri; Ramdan Panigoro (The Prodia Education and Research Institute (PERI), 2020)
BACKGROUND: Iron-overload cardiomyopathy (IOC) is a major comorbidity in patients with chronic repetitive blood transfusion due to myocardial iron uptake that facilitated by calcium channels. As cardiac compensatory mechanism to IOC, we hypothesized the cardiac calcium channels expression would be increased and involved in cardiomyopathy progressivity. This study was aimed to investigate the gene expression of calcium channels in the heart of the iron overload mice model.METHODS: Mice were divided into three groups according to iron administration doses 0, 0.1, and 0.3 mg/day. Systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP) were measured for the representation of cardiovascular outcomes. The heart tissues were harvested. Further mRNA levels of L-type calcium channels (LTCCs) and T-type calcium channels (TTCCs) were examined using semi-quantitative PCR. The expressions of cardiac calcium channels and blood pressure among the three groups were compared.RESULTS: The expressions of TTCCs in the two iron-injected groups were higher than the control group (p=0.018). The expressions of LTCCs were not different (p=0.413) among groups. SBP, DBP, and MAP of the iron-injected group were lower than the control group (p=0.025, p=0.011, and p=0.008, respectively).CONCLUSION: Iron administration affects the expression of TTCCs but not the LTCCs, accompanied by decreasing of systolic and diastolic blood pressure.KEYWORDS: cardiomyopathy, iron overload, L-type calcium channel, T-type calcium channel.